Impact Du Conseil Agricole Sur Les Performances Des Producteurs D’anacarde De Cote d’Ivoire - Doukouré Charles Fe; Kodjo Apollinaire Aklobessi (European Scientific Journal, ESJ, 2018)
The cashew sector has been booming in Côte d'Ivoire for the last three years. In the face of international competition, it appeared important to improve the performance of producers in order to maintain the comparative advantages of Côte d'Ivoire. In this perspective, the agricultural advisory project was set up to train cashew farmers in good practices. This study aims to evaluate the impact of this project on their performance in terms of returns. The data used for the analysis come from the survey conducted by the National Agency for Rural Development (ANADER). The average effect was estimated trough the propensity score matching method by using the kernel method. The results reveal that the advice and training support of cashew producers has led to a significant increase in yield of 22.4% on average.